2013
DOI: 10.3892/ijmm.2013.1341
|View full text |Cite
|
Sign up to set email alerts
|

Tougu Xiaotong capsule inhibits the tidemark replication and cartilage degradation of papain-induced osteoarthritis by the regulation of chondrocyte autophagy

Abstract: The tidemark is located between calcified and non-calcified cartilage matrices. Tidemark replication plays an important role in the pathogenesis of osteoarthrosis (OA). Autophagy, or cellular self-digestion, is an essential cellular homeostasis mechanism that was found to be deficient in osteoarthritic cartilage. This study evaluated the effects of Tougu Xiaotong capsule (TXC) on the tidemark replication and cartilage degradation, and also investigated LC3 I/II, which executes autophagy, the potential role of UL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Accordingly, the development of novel drugs from natural herbs, which can provide cartilage protection and be safely used in the prolonged treatment of OA, is required. TXC has been used to control tidemark replication and cartilage degradation by inhibiting chondrocyte apoptosis and promoting chondrocyte autophagy (18,19). Therefore, in the present study, we sought to determine the efficacy of TXC on chondrocyte autophagy, as a chondroprotective agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the development of novel drugs from natural herbs, which can provide cartilage protection and be safely used in the prolonged treatment of OA, is required. TXC has been used to control tidemark replication and cartilage degradation by inhibiting chondrocyte apoptosis and promoting chondrocyte autophagy (18,19). Therefore, in the present study, we sought to determine the efficacy of TXC on chondrocyte autophagy, as a chondroprotective agent.…”
Section: Discussionmentioning
confidence: 99%
“…The number of lysosomes increases in the process of autophagy, accompanied by an increased expression of beclin 1 and LC3 (33). Beclin 1, forming a complex with type III PI3 kinase and Vps34, participates in the nucleation of the autophagic vesicle (19). The involvement of LC3 in the protein conjugation system is required in the expansion of the autophagosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGXTC, a traditional Chinese medicine, has been demonstrated to be clinically effective in the treatment of OA, which has been indicated by in vitro and in vivo studies where TGXTC was observed to reverse cartilage degeneration in OA (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, whether TGXTC has a protective effect on subchondral bone remodeling remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The Tougu Xiaotong capsule (TGXTC), characterized as a multi-target and multi-channel compound (11), contains a proven recipe for OA treatment, consisting of Morinda officinalis, Paeonia lactiflora, Ligusticum chuanxiong and Sarcandra glabra (12). Previous studies have demonstrated that this compound may inhibit chondrocyte apoptosis, promote chondrocyte proliferation (13)(14)(15)(16), suppress expression of matrix metalloproteinases and inflammatory cytokines (17)(18)(19), improve the structure and function of cartilage (20) and promote osteoblast proliferation and activation (21). However, the regulatory effects of TGXTC on subchondral bone remodeling remain largely unclear.…”
Section: Protective Effects Of the Tougu Xiaotong Capsule On Morphologymentioning
confidence: 99%